2003
DOI: 10.1007/s00244-002-2023-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Effects of Lead in Young and Adult Fisher 344 Rats

Abstract: Abstract. Lead poisoning has been extensively studied over the years. Many adverse physiological and behavioral impacts on the human body have been reported due to the entry of this heavy metal. It especially affects the neural development of children. The current study investigates the effect of lead exposure in young (1.5 months) and adult (10 months) male Fisher 344 rats. Five weeks of lead administration resulted in a profound change in the lead levels in the red blood cells (RBCs) of the young lead-expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 20 publications
6
25
0
1
Order By: Relevance
“…Depletion of tissue GSH is one of the primary factors that permit lipid peroxidation [27]. Results of the present work show significant decrease of GSH concentrations in the erythrocyte haemolysate of lead-exposed mice which is in line with previously published works [23,28,29]. Pb +2 binding to sulfhydryl groups can reduce GSH levels and can interfere with its antioxidant activity [18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Depletion of tissue GSH is one of the primary factors that permit lipid peroxidation [27]. Results of the present work show significant decrease of GSH concentrations in the erythrocyte haemolysate of lead-exposed mice which is in line with previously published works [23,28,29]. Pb +2 binding to sulfhydryl groups can reduce GSH levels and can interfere with its antioxidant activity [18].…”
Section: Discussionsupporting
confidence: 90%
“…It is widely accepted that pollutant-induced reactive oxygen species (ROS) generation can initiate or promote lipid peroxidation. Lead-induced enhancement of thiobarbituric acid reactive substances (TBARS) have been reported in some tissues of animals [21][22][23][24][25] that can be due to the generation of ROS without commensurate increases in the level of antioxidant defenses [26]. Results of the present work showed a significant increase of MDA concentrations in the erythrocyte haemolysate of Pb-exposed mice.…”
Section: Discussionsupporting
confidence: 50%
“…Similarly, Aykin-Burns et al (2003) described that GSH levels in the brains of Pb-treated groups were found to be lower than in the control. 65) However, the concurrent treatment of Chlorella prevented GSH depletion, indicating the activity of a protective antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids are known to be involved in two important physiological functions: modulation of the immune system and detoxification . For example, heavy metals are known to produce oxidative stress in humans and animals, probably by disturbing the antioxidant-based defense of the body (Stohs and Bagchi, 1995;Mateo and Hoffman, 2001;Aykin-Burns et al, 2003). Food-derived antioxidants are consumed when the defense system is activated, and high amounts of pollutants in the body may lead to a depletion of antioxidants (Polidori et al, 2001;Krinsky and Yeum, 2003;Stehbens, 2003).…”
Section: Introductionmentioning
confidence: 99%